2021
DOI: 10.3389/fpsyt.2021.674707
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Correlates of Impulsive Aggressive Behavior in Pediatric Bipolar Disorder

Abstract: Background: Impulsive aggression represents a frequent characteristic of pediatric bipolar disorder (PBD). Cortical alterations associated with impulsive aggression and its multiple facets have not been investigated yet in youth with bipolar disorder.Aim: To investigate the relationship between cortical thickness and facets of impulsive aggression in youth with PBD.Materials and Methods: Twenty-three youth with PBD and 23 healthy controls (HC) were administered the aggression questionnaire (AQ) and underwent 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…This suggested that the partial SLF abnormalities may contribute to manic-hostility symptoms. A previous study reported that greater thickness in the frontoparietal network was positively correlated with hostility score in patients with BD ( 55 ). There was no published literature on the association between manic-hostility symptoms and microstructural changes of SLF in mental disorders.…”
Section: Discussionmentioning
confidence: 95%
“…This suggested that the partial SLF abnormalities may contribute to manic-hostility symptoms. A previous study reported that greater thickness in the frontoparietal network was positively correlated with hostility score in patients with BD ( 55 ). There was no published literature on the association between manic-hostility symptoms and microstructural changes of SLF in mental disorders.…”
Section: Discussionmentioning
confidence: 95%
“…For example, the PCC, right TPJ, MPFC, and left DLPFC are significantly activated in aggressive responses, and their morphological features can also predict aggressive tendencies [20,55,56,72,73]. Moreover, brain structural characteristics in these regions positively correlate with some negative traits that promote aggression, such as Machiavellianism [20,21,74]. These findings imply that the PCC, right TPJ, MPFC, and left DLPFC represent important components of the neural basis for the approach system of aggression.…”
Section: Discussionmentioning
confidence: 87%
“…Offspring of BD I were reported to have a thinner cortex in the right supramarginal gyrus ( Hanford et al, 2016 ), and a higher level of neuroinflammation was observed to be related to a lower volume in the right supramarginal gyrus in BD I ( Tsai et al, 2021 ). Simonetti et al proposed reduced thickness in the right supramarginal gyrus and a correlation with the subscales (anger and hostility) of aggression questionnaire in pediatric BD ( Simonetti et al, 2021 ), the type of which was not divided, although majorities were BD I. Therefore, this may explain why BD I has a higher impulsivity rate than BD II ( Izci et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%